2021
DOI: 10.4064/aa200520-22-12
|View full text |Cite
|
Sign up to set email alerts
|

Extreme and periodic $L_2$ discrepancy of plane point sets

Abstract: We study several discrepancy notions of two wellknown instances of plane point sets, namely the Hammersley point set and rational lattices. The discrepancies are considered with respect to the L 2 norm and a variety of test sets. We define (standard) L 2 discrepancy, extreme L 2 discrepancy and periodic L 2 discrepancy. Let P = {x 0 , x 1 ,. .. , x N −1 } be an arbitrary N-element point set in the unit square [0, 1) 2. For any measurable subset B of [0, 1] 2 we define the counting function A(B, P) := n ∈ {0, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 22 publications
(49 reference statements)
1
29
0
Order By: Relevance
“…Recently it has been shown that the extreme discrepancy is dominated – up to a multiplicative factor that depends only on p and d – by the star discrepancy (see [ 21 , Corollary 5]), i.e., for every and , there exists a positive quantity such that for every and every N -element point set in , we have For , we even have for all ; see [ 17 , Theorem 5]. A corresponding estimate the other way round is in general not possible (see [ 17 , Section 3]). So, in general, the star and the extreme discrepancy for are not equivalent, which is in contrast to the -case.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently it has been shown that the extreme discrepancy is dominated – up to a multiplicative factor that depends only on p and d – by the star discrepancy (see [ 21 , Corollary 5]), i.e., for every and , there exists a positive quantity such that for every and every N -element point set in , we have For , we even have for all ; see [ 17 , Theorem 5]. A corresponding estimate the other way round is in general not possible (see [ 17 , Section 3]). So, in general, the star and the extreme discrepancy for are not equivalent, which is in contrast to the -case.…”
Section: Introductionmentioning
confidence: 99%
“…For every and , there exists a such that for every finite N -element point set in with , we have For the star discrepancy, the result for is a celebrated result by Roth [ 29 ] from 1954 that was extended later by Schmidt [ 31 ] to the case . For the extreme discrepancy, the result for was first given in [ 17 , Theorem 6] and for , in [ 21 ]. Halász [ 15 ] for the star discrepancy and the authors [ 21 ] for the extreme discrepancy proved that the lower bound is even true for and , i.e., there exists a positive number with the following property: for every N -element in with , we have On the other hand, it is known that for every and every , there exist N -element point sets in such that (For , we write if there exists a positive number C such that for all .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations